The Émbu Tradition in Madura: Integration of Islamic Values and Local Wisdom in Trading - Imam Wahyudi; Ika Oktaviana Dewi; Nanang Setiawan; Risky Mezi Muria; Riskiyatur Rohemah; Isrotun Naila; Sitti Maisaroh (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
This study aims to examine the integration of Islamic values and local wisdom in the Émbu tradition in Madura which is applied in trade practices. The Émbu tradition is a manifestation of cultural locality that reflects the values of honesty, trust, and togetherness, which are in line with Islamic teachings. The study used a qualitative approach with field study methods and in-depth interviews with traders in Madura who still practice this tradition. The results of the study show that the Émbu tradition not only strengthens social relations among trading communities, but also creates an ethical and harmonious trading atmosphere, which contributes to consumer trust. The integration of this tradition with Islamic values enriches trade practices, while maintaining the cultural identity of Madura. The impact of this study is to provide insight into how local traditions can support economic development based on spiritual values, while also being a model for other regions with similar traditions